Perlindungan Hukum terhadap Investor dalam Pasar Modal Syariah di Indonesia - Rizal Maulana (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Islamic capital market is one of the rapidly growing investment instruments in Indonesia, offering investment alternatives that are in accordance with sharia principles. However, legal protection for investors in the Islamic capital market still faces various challenges that can affect investor confidence and participation. This study aims to analyze the legal protection mechanisms available to investors in the Islamic capital market and evaluate the effectiveness of the regulations that govern it. The research method uses a normative and empirical legal approach with a study of regulatory documentation and in-depth interviews with regulators, capital market players, and investors. The results of the study indicate that investor protection regulations in the Islamic capital market are formally adequate, but implementation in the field is still constrained by a lack of socialization, investor understanding, and suboptimal supervision. In addition, differences in interpretation of sharia principles in investment instruments are a challenge in themselves. The conclusion of the study emphasizes the need to improve investor education, harmonize regulations, and strengthen supervisory institutions to create a safe and transparent Islamic capital market. Recommendations are submitted for the government and related authorities to continue to improve policies and protection mechanisms in order to strengthen the Islamic investment ecosystem in Indonesia.